HEURISTIC POSSIBILITIES OF IN RESEARCH CO-OPERATIONS OF ECONOMIC SUBJECTS INSITUCIONALISM - О. Belokrulova; К. Belokrulov (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The possibilities of institutionalism are explored as an interdisciplinary methodology, synthesizing the modern achievements of philosophy and political science, economic theory, institutional economics and sociology, which describes the interactions between economic subjects more accurately, including the goverment and business on the market of public procurement. There are received solutions for problem situations in the system of the russian public procument on the way of institutionalization of centralized model on the micro level (for example, the Southern Federal University), as well as on the macrolevel in the frame of formation of Federal Contract System, aimed to integrate all stages of goverment contracting – planning, placing the order, controlling and enforcement of state contract.